Manufacturer Collusion and Resale Price Maintenance* - Matthias Hunold; Johannes Muthers (The Journal of Industrial Economics, 2024)
We provide a novel theory of harm for resale price maintenance (RPM). In a model with two manufacturers and two retailers, we show that RPM facilitates manufacturer collusion when retailers have alternatives to selling a manufacturer's product. Because of the alternatives, manufacturers can only ensure that retailers sell their products by leaving sufficient retail margins. This restricts the wholesale price level even when the manufacturers collude. RPM allows colluding manufacturers to establish higher prices.
Keywords: 330